Systemic lupus erythematosus presenting with bullous lesions, cutaneous vasculitis and laryngeal ulcerations-a rare association - Pulletikurti, Mrudula; Gopal, K. V. T.; Raju, P. V. Krishnam; Rani, B. Rekha (International Journal of Research in Dermatology, 2022)
Bullous SLE is an uncommon complication of SLE with autoantibodies to type VII collagen of dermo-epidermal junction. We report a 31-year-old female who presented with vesiculobullous lesions in the photo exposed areas along with vasculitic lesions over palms and soles and ulcerations in the larynx. She also had history of photosensitivity and hair loss. Investigations showed significant anaemia and high titres of antibodies (ANA, anti-ds-DNA, anti Sm) confirming SLE. Histopathology showing sub epidermal blister with neutrophils and immunofluorescence favoured diagnosis of bullous SLE. The patient responded well to high dose parenteral steroids and dapsone. In view of high probability of renal involvement, patient was referred to nephrologist and is under regular follow up.